(untitled) (European Journal of Formal Sciences and Engineering, 2023)
The new media concept, which emerged with the rapid change of technology, has also changed the perception of society to mass media. It is an absolute reality that the changing radio concept in the digitizing period has changed and transformed the listener along with it. It has also reformed the new media audience, which has been reformed with the convergence of mass media with technology, not only as an audience but also as a participant. As a result of convergence, new concepts such as interaction, synchronicity and mass unification have emerged. While interaction in the traditional media is provided at a limited level, content in the new media is often determined by the audience. From the point of view of new media and user relations, radio has become the medium of communication that can adapt to this change in the easiest way and change contents in this direction. the Internet has offered a radio technology to radio listeners that allows the radio to establish its own radio. All these technological developments and the activation of the audience have reshaped the radio and listener relationship. The main aim of this study is to reveal how the radio, a warm communication medium, is shaped its own language and the relationship established with the audience through technology. In this direction, a structured in-depth interview will be held with 24 people working at Anadolu University in February 2018. These people will be randomly determined according to their socio-economic status. According to the Socio-economic Statutes, 8 faculty members, 8 civil servants and 8 workers will be selected. The selected sampling will ask questions such as radio listening habits, why they listen to the radio and what the effect of participating in radio programs for a democratic society will be in order to define the link they establish with the radio.